2005
DOI: 10.1093/ejo/cjh100
|View full text |Cite
|
Sign up to set email alerts
|

Office reconditioning of stainless steel orthodontic attachments

Abstract: An investigation was conducted to determine a simple, effective method for reconditioning stainless steel orthodontic attachments in the orthodontic office. In total, 100 new brackets were bonded to premolar teeth, then debonded and the bond strength recorded as a control for the reconditioning process. The debonded brackets were divided into six groups and each group reconditioned using different techniques as follows: attachments in four groups were flamed and then either (1) sandblasted, (2) ultrasonically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 17 publications
5
41
3
4
Order By: Relevance
“…The results found no significant differences in SBS between the four study groups after brackets were recycled for the first time, a finding that agrees with other studies that have evaluated SBS after rebonding new brackets and brackets reconditioned by micro sandblasting 15,17,20 or by industrial methods. 7 However, Chung et al 21 found that brackets reconditioned by sandblasting needed a bond booster to prevent a loss of SBS compared with new brackets.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results found no significant differences in SBS between the four study groups after brackets were recycled for the first time, a finding that agrees with other studies that have evaluated SBS after rebonding new brackets and brackets reconditioned by micro sandblasting 15,17,20 or by industrial methods. 7 However, Chung et al 21 found that brackets reconditioned by sandblasting needed a bond booster to prevent a loss of SBS compared with new brackets.…”
Section: Discussionsupporting
confidence: 89%
“…Research comparing reconditioning methods used in the clinic has concluded that sandblasting is the most effective method for removing bond material, while no significant differences in bond strength were identified between brackets recycled by this means and new brackets. [15][16][17] Studies of brackets that have undergone successive recycling show contradictory results. Regan et al 18 found no significant differences in SBS among metal brackets that had been recycled up to five times, while Buchwald 5 found that the percentage of brackets that could be reused decreased with each successive recycle.…”
Section: Introductionmentioning
confidence: 99%
“…Several in-office reconditioning methods have been introduced. 10,11,20 These processes include mechanical methods (hand pieces with rotary burs, chair-side sandblasting), thermal methods (direct flaming or heating in a furnace), and a combination of the two (direct flaming to burn off the composite, followed by sandblasting and electropolishing). 10 Quick et al…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be useful if the orthodontist could manage the in-office reconditioning processes without affecting the shear bond strength (SBS) of these brackets. To date the literature contains many published articles 1,10,11 that involved testing the SBS of new vs reconditioned brackets, but there are no studies that have involved evaluation of the effect of the reconditioning process on the SBS of the newgeneration self-ligating orthodontic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…Method of recycling process is time consuming. Lower SBS of recycled brackets in some methods such as using direct flame [8].…”
Section: Bracket Recyclingmentioning
confidence: 99%